Effects of innovation diffusion on the development level for some European regions in the expansion period of the European Union - Gündüz Atalik; Seda Kundak (European Regional Science Association (ERSA), 2004)
It is argued that innovation diffusion, in other words the movement of the new ideas or articrafts within an area over a number of time periods could become widespread once introduced in the area. After Schumpeter the role of the innovator has been significant as the inventor, as the developer or as the promoter. It is clear now that a number of economists have one thing in common that profit rates would be pushed to minimal levels in the absence of technical development. In fact, in the new theories of development concepts related to knowledge development and its diffusion take precedence. Moreover, concerning regional disparities and regional convergence issues in the European Union, it is pointed out that R&D investment in lagging areas could be the only way to avoid technology and development divergence between core and periphery. In this connection, it might be worthwhile to consider the enlargement process of the European Union with further expansion period. In this way, the objective of this article will be to find out probable effects of R&D on the development level in a five-years period (1996-2001) in order to examine the efficiency rate of innovation diffusion on the development level and to derive some theoretical and practical results.
Keywords: 330